Locating the beginnings of pain. - Derbyshire SW (Bioethics, 1999)
This paper examines the question of whether a fetus can feel pain. The question is divided into four sub questions: What is pain? What is the neurology of pain processing? What is the fetus? Are there good reasons for holding that fetuses feel pain? Pain is suggested to be a multi-dimensional phenomenon drawing on emotional and sensory processes--a consequence of a gradual development involving a number of noxious events rather than an automatic consequence of injury or disease. The nonautomaticity of pain is emphasised in the discussion of pain neurology that defies explanations based on a specialised neuronal `pain-centre'. The development of the fetus is considered with respect to developmental neurobiology, behavioural and neurological responses to stimulation, and hormonal and neurochemical responses to noxious stimulation. While acknowledging that the development of the fetus is complex, especially after 26 weeks gestation, considerable development is still to occur, even after birth. The fetal pain literature is criticised for tending to exaggerate fetal development. Finally, the difficulty of explaining the subjectivity of pain in materialist terms is discussed. Pain is suggested to arise with development of the necessary neurological, cognitive and emotional structures. Pain experience is placed at approximately 12 months of age, though this is within the context of a continuum of awareness rather than a straight `on-off' switch. The major moral implication of this stance is to place the burden of proof for analgesic use onto clinical measures, rather than relying upon the, so far, poorly supported assumption of pain awareness.